2001
DOI: 10.1089/02724570152057634
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Clinical Evaluation of a Neutralizing Monoclonal Antibody Against Epidermal Growth Factor Receptor in Advanced Brain Tumor Patients: Preliminary Study

Abstract: High levels of growth factors and their receptors have been demonstrated in human tumors. Gliomas and meningiomas are characterized by overexpression of epidermal growth factor receptor (EGF-R). Ior egf/r3, is a neutralizing murine monoclonal antibody (MAb) against EGF-R, and was generated at the Cuban Institute of Oncology. The antibody recognizes EGF-R with high affinity, inhibiting tyrosine kinase activation. A clinical trial was conducted in brain tumor patients to evaluate toxicity, immunogenicity, and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…However, there are clinical observations suggesting that short-term mechanisms such as EGFR signaling inhibition and Ab-dependent cellular cytotoxicity are not the only ones involved. Some studies have indicated that maximal clinical and molecular responses to anti-EGFR Abs may take several months (35)(36)(37). Mechanisms underlying the induction of long-time disease stabilization by EGFR Ab treatment have not been formally investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are clinical observations suggesting that short-term mechanisms such as EGFR signaling inhibition and Ab-dependent cellular cytotoxicity are not the only ones involved. Some studies have indicated that maximal clinical and molecular responses to anti-EGFR Abs may take several months (35)(36)(37). Mechanisms underlying the induction of long-time disease stabilization by EGFR Ab treatment have not been formally investigated.…”
Section: Discussionmentioning
confidence: 99%
“…13 Nimotuzumab has shown a synergic effect when combined with external bean radiotherapy and it has been well tolerated through the intravenous route for treating the advanced epithelial-derived cancer patients including high-grade glioma patients. [14][15][16][17] Recent data from a phase I/II clinical trial, with 200 mg/week of Nimotuzumab for 6 weeks, administered by IV infusion, combined with external radiotherapy in 24 patients with high grade astrocytoma showed no grade 3/4 adverse events. Four patients achieved complete response, 5 a partial response and 11 stable disease, while the median survival time was 22.17 months for all subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Abs in serum samples collected during the period of EPO resistance were shown to recognize each of the three recombinant EPOs this patient received-epoetin alfa, epoetin beta, and darbepoetin alpha. Specificity of the assay was confirmed by homologous and heterologous displacement (i.e., competition) with the various recombinant proteins (20,94).…”
Section: Elisamentioning
confidence: 95%
“…An indirect ELISA was used by Weber and colleagues to demonstrate the presence of anti-EPO Abs in a patient with Ab-mediated PRCA who had received multiple recombinant EPOs (20,94). Abs in serum samples collected during the period of EPO resistance were shown to recognize each of the three recombinant EPOs this patient received-epoetin alfa, epoetin beta, and darbepoetin alpha.…”
Section: Elisamentioning
confidence: 99%